Management of the Vocational Training Center Training Program - Maulani, Resmiranda; Danugiri, Dadang (Journal of Nonformal Education and Community Empowerment, 2022)
Program management is now a widely used approach to bring about the planned change and is used to implement a strategy. This study aims to observe the condition of the management of the training program at the Vocational Training Center in Subang Regency. This research approach uses a descriptive qualitative approach. There were 4 subjects in the study, consisting of 1 principal and 3 instructors. Data collection through documentation analysis techniques, interviews, and observation. Data analysis through the stages of data collection, data reduction, data presentation, and concluding. Based on the results of the research, it was concluded that planning is related to the identification of industrial needs for human resources with certain competency abilities and the determination of program objectives and learning objectives or the curriculum of each training program. Organizing training programs involves all parties to prepare training programs according to their respective duties. Organization of facilities and infrastructure is carried out to identify availability and readiness for use. The mobilization stage is in the form of preparation from the initial recruitment of training participants by predetermined conditions to the implementation of the learning process. Coaching functions to supervise and control the course of the learning process so that it continues to run according to the goals that have been set. The development of training programs is carried out to improve and perfect the previous training programs. Thus, it can improve the implementation of further training programs